Instilling Pancasila Leader Ship Character Values Through Pancasila Education With A Constructivist Approach - Sarwo Edy; Dasim Budimansyah; Encep Syarief Nurdin; Mupid Hidayat (UNIVERSITAS PAKUAN, 2025)
Pancasila and PPKn education should not only be theoretical subjects but also practical vehicles for building student character and leadership. This study aims to determine the process of instilling leadership character based on Pancasila values ​​through several constructivist approaches and their supporting factors. The research method uses qualitative research with data collection from interviews, observations, and documentation. The results of this study explain that the process of instilling leadership character based on Pancasila values ​​through several constructivist approaches, for example, through social projects and activities such as reflective discussions, actual case studies, and community activities, helps students understand how the principles of humanity, justice, and unity are applied in real life. In addition, organizational activities and leadership training on campus also strengthen these values ​​contextually. Through these activities, students are trained to be disciplined, resilient, tolerant, and able to work together with a leadership spirit based on morality and justice. Factors that support the success of this study are the existence of a relevant curriculum, active learning methods based on discussions and case studies, a disciplined and moral campus environment, and strong institutional support for student character development. However, there are several obstacles such as limited lecture time, lack of role models from some lecturers, student orientation that is still focused on academic grades, high administrative burdens on lecturers, and differences in teaching styles and diverse student backgrounds.